PENGARUH pH DAN PUTARAN PENGADUKAN PADA FERMENTASI MOLASE TERHADAP HASIL AKHIR PRODUKSI BIOETANOL (Energy, Materials and Product Design, 2022)
Until now, oil and gas are the main energy sources in the world. Indonesia is a country with high energy utilization. Energy sources in Indonesia still come from fossil fuels. Burning fossil fuels, such as oil and gas, can cause the greenhouse effect. Therefore we need an alternative energy (biofuel) that is not harmful to the ecosystem. One example of biofuel is bioethanol. This study used 2 variations, namely stirring rotation (800, 1000 and 1200 rpm) and fermentation pH (4, 4.5 and 5). So from the two variations, 9 kinds of treatment were obtained with 3 repetitions so that the total sample was 27. The purpose of this study was to determine the effect of stirring rotation (rpm) and pH of fermentation on the final yield of bioethanol production. The production of bioethanol is carried out by a fermentation process for 48 hours, then distilled to obtain bioethanol.  The results of this study indicate that the variation of fermentation pH is the most dominant factor on the level of bioethanol produced, while for the volume of bioethanol produced the most dominant factor is the stirring rotation. The treatment that produced the highest volume of bioethanol was a stirring rotation of 1000 rpm and a fermentation pH of 4 with an average volume of 1234.3 mL and the highest alcohol content was obtained at a stirring rotation of 1000 Rpm and a fermentation pH of 5 with an average value of 81.3%.
Keywords: Bioethanol, stirring rotation, pH of fermentation, molasses.